Time capsule description, Spokane, Washington : statehood Centennial : - Swinton, Duane M.
In celebration of Washington State's Centennial, a time capsule was buried in Riverfront Park in the Couplet Meadow on Nov. 11, 1989. The 50 items buried in the capsule include: By the falls: Women of determination, Spokane: Children of the Sun commemorative poster, and a 1989 Bloomsday T-shirt.